Особенности скоростного плавления и затвердевания неметаллических включений в стали при лазерном воздействии - Губенко, С.И. (Вісник Українського матеріалознавчого товариства, 2017)
The laser action produces melting and high-speed crystallization of inclusions, which contributes to the formation of an ultrafine-grained structure with a columnar shape of grains, the appearance of shear zones and dispersed particles of new phases. The structural features of gradient and composite zones in a steel matrix near nonmetallic inclusions and their influence on hardening of steels under laser action are established. The results obtained will make it possible to develop methods and regimes of laser processing that allow to influence on the dimensions, composition, structure and distribution of nonmetallic inclusions in steels in order to improve mechanical properties.